2010
DOI: 10.1002/art.27572
|View full text |Cite
|
Sign up to set email alerts
|

A novel autoantibody recognizing 200‐kd and 100‐kd proteins is associated with an immune‐mediated necrotizing myopathy

Abstract: Objective. Myofiber necrosis without prominent inflammation is a nonspecific finding in patients with dystrophies and toxic or immune-mediated myopathies. However, the etiology of a necrotizing myopathy is often obscure, and the question of which patients would benefit from immunosuppression remains unanswered. The aim of this study was to identify novel autoantibodies in patients with necrotizing myopathy.Methods. Muscle biopsy specimens and serum samples were available for 225 patients with myopathy. Antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

22
398
8
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 452 publications
(456 citation statements)
references
References 22 publications
22
398
8
28
Order By: Relevance
“…This supports the recently published diagnostic algorithm by Mammen et al, [14] which recommends serological testing for anti-HMGCR antibodies prior to muscle biopsy. Given the specificity of positive anti-HMGCR antibodies for NAM in the context of patients over 50 years with previous stain exposure [6,18,19], perhaps future diagnoses could be based on clinical picture and serology alone, without the need for invasive muscle biopsies. All patients were screened clinically for malignancy and 40% of our cohort received formal malignancy screening including either PET or CT imaging of chest, abdomen, pelvis, although no patients were found to have malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the recently published diagnostic algorithm by Mammen et al, [14] which recommends serological testing for anti-HMGCR antibodies prior to muscle biopsy. Given the specificity of positive anti-HMGCR antibodies for NAM in the context of patients over 50 years with previous stain exposure [6,18,19], perhaps future diagnoses could be based on clinical picture and serology alone, without the need for invasive muscle biopsies. All patients were screened clinically for malignancy and 40% of our cohort received formal malignancy screening including either PET or CT imaging of chest, abdomen, pelvis, although no patients were found to have malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Deposition of complement membrane attack complexes on non-necrotic muscle fibers is consistent with the concept that the myofiber degeneration in anti-HMGCR NAM is a complement-mediated antibody-dependent toxicity. 12 Additionally, there is an identified association between anti-HMGCR NAM and HLA-DRB1*11. 13 The novel anti-HMGCR antibody, which was discovered in 2010, is a promising diagnostic marker for statin-associated NAM.…”
Section: Discussionmentioning
confidence: 99%
“…13 The novel anti-HMGCR antibody, which was discovered in 2010, is a promising diagnostic marker for statin-associated NAM. 12 Nearly all patients with statin-induced necrotizing . This confirms that during the early antibody-mediated phase of the disease, the membrane is relatively intact, but in later phases, the membrane integrity is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent case series have suggested that anti-SRP levels do correlate with disease severity, and may serve as a marker of poor prognosis [13,14] . Additionally, a recent study identified anti-HMGCoA reductase autoantibodies in 63% of patients with necrotizing autoimmune myopathy [15] . These antibodies are more frequently found in patients with statin-associated necrotizing myopathy, and less frequently in statin-unexposed subjects [16] .…”
Section: Discussionmentioning
confidence: 99%